A diazirine-based photoaffinity etoposide probe for labeling topoisomerase II - Chee, Gaik-Lean (2009)
Etoposide is a widely used anticancer drug that targets topoisomerase II, an essential nuclear enzyme. However, despite the fact that it has been in use and studied for more than 30 years the specific site on the enzyme to which it binds is unknown. In order to identify the etoposide binding site(s) on topoisomerase II, a diazirine-based photoaffinity etoposide analog probe has been synthesized and its photoreactivity and biological activities have been characterized. Upon UV irradiation, the diazirine probe rapidly produced a highly reactive carbene species that formed covalent adducts containing stable carbon-based bonds indicating that it should also be able to form stable covalent adducts with amino acid residues on topoisomerase II. The human leukemia K562 cell growth and topoisomerase II inhibitory properties of the diazirine probe suggest that it targets topoisomerase II in a manner similar to etoposide. The diazirine probe was also shown to act as a topoisomerase II poison through its ability to cause topoisomerase IIα-mediated double-strand cleavage of DNA. Additionally, the diazirine probe significantly increased protein-DNA covalent complex formation upon photoirradiation of diazirine probe-treated K562 cells, as compared to etoposide-treated cells. This result suggests that the photoactivated probe forms a covalent adduct with topoisomerase IIα. In conclusion, the present characterization of the chemical, biochemical, and biological properties of the newly synthesized diazirine-based photoaffinity etoposide analog indicates that use of a proteomics mass spectrometry approach will be a tractable strategy for future identification of the etoposide binding site(s) on topoisomerase II through covalent labeling of amino acid residues.